Currency Substitution via Expected Exchange Rate and Domestic Money Demand: An Empirical Analysis for Japan - Chotigeat, T.; Sang, H. Lee (Universiti Putra Malaysia Press, 1996)
In this paper the currency substitution hypothesis is tested empirically on the Japanese money demand, using monthly data from January 1977 to December 1989. Under a flexible exchange rate a rational economic agent forms currency portfolios for both transaction and speculative reasons for demanding money. The nonlinear multivariate maximum likelihood estimation was used to estimate jointly the Japanese money demand and the expected exchange rate equation; possible existence of current substitution is found. The empirical results indicate that (a) the expected exchange rate for the Japanese yen/Canadian dollar shows currency substitution due to speculative demand, and (b) the expected exchange rate of the yen/US dollar shows currency substitution due to transaction demand.